Effects of lacosamide and carbamazepine on lipids in a randomized trial. (17th November 2020) - Mintzer, Scott; Dimova, Svetlana; Zhang, Ying; Steiniger‐Brach, Björn; De Backer, Marc; Chellun, Daya; Roebling, Robert
Abstract: Objective: The effects of anticonvulsants on lipids are the subject of considerable concern and investigation, but there are almost no data on this issue from randomized trials. We evaluated serum lipid profiles in adults with newly diagnosed epilepsy, following randomization to lacosamide (LCM) or carbamazepine (CBZ) monotherapy. Methods: We analyzed data from a Phase 3, international, randomized, double‐blind trial of LCM vs CBZ for the initial treatment of focal epilepsy. Serum lipid profiles in patients not taking lipid‐lowering agents and providing blood samples under fasting conditions before treatment, and following 3 or 12 months of treatment with LCM or CBZ at various doses were analyzed. Results: At 12 months, 271 patients satisfied the inclusion criteria for the analysis. No change was observed in LCM‐treated patients for total cholesterol, cholesterol fractions, or triglycerides. CBZ‐treated patients showed an increase of 21.1 mg/dL in total cholesterol, 12.6 mg/dL in low‐density lipoprotein (LDL) cholesterol, 12.5 mg/dL in non–high density lipoprotein (non‐HDL) cholesterol, and 8.5 mg/dL in HDL cholesterol; triglycerides remained unchanged. The proportion of patients with elevated total cholesterol levels (above the upper limit of the reference range) did not change in the LCM treatment group (37.0% at Baseline; 34.8% at 12 months), but increased from 30.8% (at Baseline) to 49.6% (at 12 months) in the CBZ treatment group. Significance: This study provides Class II evidence that CBZ elevates serum lipids, whereas LCM has no effect on lipids. It supports LCM as an appropriate choice for new‐onset focal epilepsy.